Effects of Several Cultivars', Mulch and Fertilizer Applications on Plant Growth and Development Criteria and Plant's Nutrition Elements Uptake in Organic Strawberry Plantation in Nevşehir City - Şener , Sevinç; Türemiş, Nurgül F (Asian Journal of Agriculture and Rural Development, 2017)
This study was conducted to investigate the effect of different mulch types’ (black plastic, textile and sawdust) and fertilizer applications (Ekoflora, Mog, Bio-one, Ferbanat L and Natural Bioplasma) effect in strawberry (Fragaria vesca L.) cultivars (‘Monterey’, ‘Albion’, ‘Aromas’, ‘Camarosa’ and ‘Sweet Charlie’). The effects of applications on plant nutrient concentrations (N, P, K, Ca, Mg and Fe) and plant growth and development criteria (plant height, steam diameter, number of leaf and root height) were determined. Fertilizer material and cultivars caused significant differences in the plant growth and development of five strawberry cultivars, while mulch materials’ effects found only on number of leaf and root height. Highest values in terms of plant growth and development criteria were found in ‘Camarosa’ cultivar and black plastic and textile mulch. The most superior cultivar in terms of plant's nutrition elements uptake was ‘Camarosa’. Black plastic and textile mulch were found more advantageous compared to sawdust mulch. Differences in the plant growth and development criteria and plant's nutrition elements uptake obtained from fertilizer applications were noted.